Composite glass fiber separator and method of making the same

CN117613506BActive Publication Date: 2026-10-27SHAANXI UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311589595.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-27
Publication Date
2026-10-27
Estimated Expiration
2043-11-27

AI Technical Summary

Technical Problem

[0006]本发明要提供一种复合玻璃纤维隔膜及其制备方法,以解决现有技术中存在的在电池中易脱落,不利于电池中锂金属电极侧锂离子的均匀传输以及固体电解质界面的均匀沉积的问题

Benefits of technology

[0021]1.本发明首先利用层层旋喷原位热聚合方法,在玻璃纤维基底上均匀旋喷溶液,使含有多氮和氨基的晶态MOF在玻璃纤维基底上原位均匀致密地层层生长。然后用原位热聚合方法使前体溶液包覆玻璃纤维,实现了隔膜厚度的可控制备和高安全性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117613506B_ABST
    Figure CN117613506B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of electrochemistry, and particularly relates to a composite glass fiber diaphragm and a preparation method thereof. The method comprises the following steps: firstly, a MOF composite glass fiber battery diaphragm is prepared by layer-by-layer spin spraying of a metal salt solution and a ligand solution on a glass fiber substrate; and then a polymer precursor solution is used to perform in-situ thermal polymerization to form a polymer-coated sodium battery composite diaphragm. The composite glass fiber diaphragm has a capacity of 108 mAhg ‑1 after 900 cycles at a rated capacity of 1C, a coulombic efficiency of 99%, and good cycle performance. The battery has a charge transfer resistance of 68 Omega before cycle, a low initial internal resistance, and an electrochemical window of 4.84 V, realizes controllable diaphragm thickness and high safety performance, improves the safety of the diaphragm in the battery, and effectively solves the problem of uneven deposition of sodium ions. The preparation method is simple and suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical technology, specifically relating to a composite glass fiber membrane and its preparation method. Background Technology

[0002] Sodium-ion batteries are a major development direction in the battery field. As an effective alternative to lithium-ion batteries, sodium-ion batteries have promising applications in large-scale energy storage and other fields due to their potential cost advantages, thus attracting widespread research and development. However, the ionic radius of sodium ions is larger than that of lithium ions (…). vs This significantly affects the diffusion efficiency of sodium ions in the guest material.

[0003] Currently, polyethylene (PE), polypropylene (PP), and glass fiber (GF) are widely used commercial separators for lithium / sodium batteries. Glass fiber is frequently used in lithium / sodium batteries due to its high liquid absorption, low resistivity, good chemical stability, and high mechanical strength. However, its low volumetric energy density and high porosity can lead to uneven sodium dendrite formation within the battery, causing short circuits. Metal-organic frameworks (MOFs), with their abundant pores, can serve as effective fillers to ensure sodium ion migration. Combining MOFs with commercial sodium-ion battery separators shows great promise. Therefore, introducing composite separators can address the low energy density issue and improve the overall performance of the separator.

[0004] Application CN202310918816.1 discloses "A method for preparing and applying a TiN-modified glass fiber separator." The separator incorporates black TiN nanoparticles obtained from high-temperature calcined TiO2, which are then loaded onto glass fibers via vacuum filtration to prepare a modified glass fiber separator. However, this method suffers from several drawbacks: low safety in liquid batteries, and the TiN nanoparticles, physically adsorbed on the glass fibers, are prone to detachment within the battery, hindering uniform lithium-ion transport at the lithium metal electrode side and uniform deposition at the solid electrolyte interface.

[0005] In summary, the preparation of a safe, high-performance, and easily transportable battery separator is a key research direction for researchers in this field. Summary of the Invention

[0006] The present invention provides a composite glass fiber separator and its preparation method to solve the problems existing in the prior art, such as easy shedding in the battery, which is not conducive to the uniform transport of lithium ions on the lithium metal electrode side and the uniform deposition of solid electrolyte interface.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is a method for preparing a composite glass fiber diaphragm, the specific operation steps of which are as follows:

[0008] S1: Dissolve zinc nitrate hexahydrate in N,N-dimethylformamide (DMF) and disperse it by ultrasound to prepare a colorless and transparent solution A; then weigh 5-aminotetrazole and 5,6-dimethylbenzimidazole in a molar ratio of 1:1 and dissolve them in N,N-dimethylformamide, disperse them by ultrasound to prepare a light yellow and clear solution B;

[0009] S2: Place the glass fiber on the heating plate, spray solution A evenly onto it using a spray gun, let it stand and stabilize, then wash it with ethanol. Then spray solution B evenly onto it using a spray gun, let it stand and stabilize, then wash it with ethanol to obtain composite glass fiber C.

[0010] S3: At room temperature, C is immersed in DMF for 1-3 hours, removed, and then immersed in ethanol for 12-24 hours. The treated C is then dried in an oven at 120℃ to obtain glass fiber D, which is a MOF composite loaded with imidazole tetrazolium crystals.

[0011] S4: Preparation of precursor solution; Weigh 4-acryloylmorpholine monomer into a vial, then add crosslinking agent N,N-methylenebisacrylamide and initiator azobisisobutyronitrile and mix them in a mass ratio of 8:1:1 or 9:1:1. Stir evenly at room temperature to form precursor solution E;

[0012] S5: The precursor solution E is dropped into the prepared MOF composite glass fiber D, and then placed in an oven for in-situ thermal polymerization to finally obtain the composite glass fiber membrane F; after vacuum drying, it is placed in a glove box.

[0013] Furthermore, in step 1 above, the ultrasound time is 10-15 minutes.

[0014] Furthermore, in step 2 above, the temperature of the heating plate is 120-150℃, and the distance between the spray gun and the glass fiber is 8-10 cm.

[0015] Furthermore, in step 2 above, the spraying time for solution A is 20-30 seconds and the stabilization time is 10-20 seconds, while the spraying time for solution B is 30-40 seconds and the stabilization time is 20-30 seconds.

[0016] Furthermore, in step 5 above, the temperature of the oven is 65-80℃.

[0017] Furthermore, in step 5 above, the vacuum drying temperature is 60-80℃, and the oxygen content in the glove box is not higher than 0.01ppm.

[0018] Furthermore, in step 5 above, for the 2032 button cell, the D size of the MOF composite glass fiber is 19 mm, and the amount of the added precursor solution is not less than 100 μl.

[0019] Furthermore, in step 5 above, for pouch batteries, the size of the glass fiber D in the MOF composite is 4cm*4cm, and the amount of the added precursor solution is not less than 500μl.

[0020] Compared with the prior art, the beneficial effects of the present invention are:

[0021] 1. This invention first utilizes a layer-by-layer spin-spray in-situ thermal polymerization method to uniformly spin-spray a solution onto a glass fiber substrate, enabling the in-situ, uniform, and dense layer-by-layer growth of crystalline MOFs containing polynitrogen compounds and amino groups on the glass fiber substrate. Then, an in-situ thermal polymerization method is used to coat the glass fibers with the precursor solution, achieving controllable preparation of the membrane thickness and high safety performance.

[0022] 2. The polynitrogen units of this invention endow the crystalline MOF with strongly polarized channels and high thermal and chemical stability. The amino functional groups in the MOF have strong electron-withdrawing capabilities, enabling controllable electron distribution within the membrane and achieving Na… + Targeted migration of Na+ effectively promotes Na+ migration. + Transport within the separator. In-situ polymerization of a precursor solution on composite glass fibers forms a 3D cross-linked network that coats the glass fibers, improving the interfacial resistance between the separator and the electrodes, thereby effectively enhancing the separator's safety within the battery.

[0023] 3. The N coordination environment in the multi-nitrogen MOF of this invention is abundant, providing more active sites. Increasing the density of active sites effectively improves battery performance. Furthermore, the controllable distribution of electrons is achieved through the modification of the MOF with strong electron-withdrawing amino groups, thereby constructing a separate sodium ion orientation channel. This specific channel effectively solves the problem of uneven sodium ion deposition, enabling directional migration of sodium ions and ultimately suppressing lithium dendrite formation.

[0024] 4. The composite glass fiber membrane prepared by this invention, after 900 cycles at a rated capacitance of 1C, exhibits a charge / discharge capacity of 108 mAh g at a fast-charging current density of 1C. -1 The Coulomb efficiency is 99%.

[0025] 5. The preparation method of this invention is simple. It can achieve large-scale industrial production by using a layer-by-layer rotary spray in-situ thermal polymerization method and simultaneously using a precursor solution for in-situ polymerization. Attached Figure Description

[0026] Figure 1 This is a flowchart of the preparation process of the present invention;

[0027] Figure 2 This is a SEM image of Embodiment 1 of the present invention;

[0028] Figure 3 This is a SEM image of the composite glass fiber diaphragm after thermal polymerization in Example 1 of the present invention;

[0029] Figure 4 This is a long-cycle current diagram of the sodium-ion battery assembled in Embodiment 1 of the present invention under 1C conditions;

[0030] Figure 5 This is a cycle rate diagram of the sodium-ion battery assembled in Embodiment 1 of the present invention under different current densities;

[0031] Figure 6 This is an electrochemical window diagram of the sodium-ion battery assembled in Example 1 of the present invention;

[0032] Figure 7 This is the electrochemical impedance spectroscopy diagram of the sodium-ion battery assembled in Example 1 of the present invention before cycling. Detailed Implementation

[0033] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. It should be understood that the following embodiments are only used to explain the present invention and are not intended to limit the present invention.

[0034] Example 1: A method for preparing a composite glass fiber diaphragm, see [link to example]. Figure 1 The specific steps are as follows:

[0035] Step 1: Dissolve zinc nitrate hexahydrate in N,N-dimethylformamide (DMF) and sonicate for 10 minutes to disperse it into a colorless and transparent solution A with a concentration of 0.125 mol / L. Then, weigh out 5-aminotetrazole and 5,6-dimethylbenzimidazole in a molar ratio of 1:1, dissolve them together in DMF, and sonicate for 10 minutes to disperse them into a light yellow and clear solution B with a concentration of 0.125 mol / L.

[0036] Step 2: Cut the glass fiber to a diameter of 19mm, tailored to the CR2032 battery casing. Place the glass fiber on a 120℃ heating plate, with the spray gun 10cm away from the glass fiber. Spray solution A evenly for 20 seconds, allow it to stand for 20 seconds, then wash with ethanol. Repeat this process, spraying solution B evenly for 40 seconds, allowing it to stand for 20 seconds, then washing with ethanol. Continue this in-situ spraying process for 10 cycles to obtain composite glass fiber C.

[0037] Step 3: At room temperature, C is immersed in DMF for 1 hour, then removed and immersed in ethanol for 12 hours. The composite membrane is then placed in an oven at 120°C to dry, thus obtaining composite glass fiber D loaded with imidazole-tetrazole crystalline MOF.

[0038] Step 4: Prepare the precursor solution. The mass ratio of monomer: crosslinking agent: initiator is 8:1:1. Weigh 4-acryloylmorpholine monomer and place it in a small bottle. Then add crosslinking agent N,N-methylenebisacrylamide and initiator azobisisobutyronitrile and mix. Stir evenly at room temperature to form precursor solution E.

[0039] Step 5: 100 μl of precursor solution E is dropped into the prepared MOF composite glass fiber D to uniformly encapsulate the MOF composite glass fiber D. Then, it is placed in an oven at 65°C for in-situ thermal polymerization for 6 hours to finally obtain a layer-by-layer spin-spray in-situ thermally polymerized imidazole tetrazolium crystalline composite glass fiber membrane F.

[0040] Step 6: After drying the prepared composite glass fiber diaphragm F in a vacuum drying oven at 60°C for 12 hours, remove it and place it in a glove box where the water and oxygen values ​​are both less than 0.01 ppm.

[0041] Example 2: A method for preparing a composite glass fiber diaphragm, the specific steps of which are as follows:

[0042] Step 1: Dissolve zinc nitrate hexahydrate in N,N-dimethylformamide (DMF) and sonicate for 15 minutes to disperse it into a colorless and transparent solution A with a concentration of 0.125 mol / L. Then, weigh out 5-aminotetrazole and 5,6-dimethylbenzimidazole in a molar ratio of 1:1, dissolve them together in DMF, and sonicate for 15 minutes to disperse them into a light yellow and clear solution B with a concentration of 0.125 mol / L.

[0043] Step 2: Cut the glass fiber to a diameter of 19mm, tailored to the CR2032 battery casing. Place the glass fiber on a 125℃ heating plate, with the spray gun 10cm away from the glass fiber. Spray solution A evenly for 20 seconds, allow it to stand for 20 seconds, then wash with ethanol. Repeat this process, spraying solution B evenly for 40 seconds, allowing it to stand for 20 seconds, then washing with ethanol. Continue this in-situ spraying process for 10 cycles to obtain composite glass fiber C.

[0044] Step 3: At room temperature, C is immersed in DMF for 2 hours, then removed and immersed in ethanol for 12 hours. The composite membrane is then placed in an oven at 120°C to dry, thus obtaining composite glass fiber D loaded with imidazole tetrazolium crystalline MOF.

[0045] Step 4: Prepare the precursor solution. The mass ratio of monomer: crosslinking agent: initiator is 8:1:1. Weigh 4-acryloylmorpholine monomer and place it in a small bottle. Then add crosslinking agent N,N-methylenebisacrylamide and initiator azobisisobutyronitrile and mix. Stir evenly at room temperature to form precursor solution E.

[0046] Step 5: 150 μl of precursor solution E is dropped into the prepared MOF composite glass fiber D to uniformly wrap the glass fiber. Then, it is placed in an 80℃ oven for in-situ thermal polymerization for 6 hours to finally obtain the layer-by-layer spin-spray in-situ thermally polymerized imidazole tetrazolium crystalline composite glass fiber membrane F.

[0047] Step 6: After drying the prepared composite glass fiber diaphragm F in a vacuum drying oven at 60°C for 12 hours, remove it and place it in a glove box where the water and oxygen values ​​are both less than 0.01 ppm.

[0048] Example 3: A method for preparing a composite glass fiber diaphragm, the specific steps of which are as follows:

[0049] Step 1: Dissolve zinc nitrate hexahydrate in N,N-dimethylformamide (DMF) and sonicate for 10 minutes to disperse it into a colorless and transparent solution A with a concentration of 0.125 mol / L. Then, weigh out 5-aminotetrazole and 5,6-dimethylbenzimidazole in a molar ratio of 1:1, dissolve them together in DMF, and sonicate for 10 minutes to disperse them into a light yellow and clear solution B with a concentration of 0.125 mol / L.

[0050] Step 2: For the CR2032 battery casing, cut the glass fiber into a circle with a diameter of 19mm. For the soft-pack battery, cut the separator sheet into a 4cm*4cm square. Place the glass fiber on a 120℃ heating plate, with the spray gun 8cm away from the glass fiber. Spray solution A evenly for 40 seconds, let it stand for 20 seconds to stabilize, then wash with ethanol. Then spray solution B evenly for 80 seconds, let it stand for 20 seconds to stabilize, then wash with ethanol. By spraying in situ five times layer by layer, composite glass fiber C is obtained.

[0051] Step 3: At room temperature, C is immersed in DMF for 1 hour, then removed and immersed in ethanol for 24 hours. The composite membrane is then placed in an oven at 120°C to dry, thus obtaining composite glass fiber D loaded with imidazole tetrazolium crystalline MOF.

[0052] Step 4: Prepare the precursor solution. The mass ratio of monomer: crosslinking agent: initiator is 9:1:1. Weigh 4-acryloylmorpholine monomer into a small bottle, then add crosslinking agent N,N-methylenebisacrylamide and initiator azobisisobutyronitrile and mix. Stir evenly at room temperature to form precursor solution E.

[0053] Step 5: 150 μl of precursor solution E is dropped into the prepared MOF composite glass fiber D to uniformly wrap the glass fiber. Then, it is placed in an 80℃ oven for in-situ thermal polymerization for 6 hours to finally obtain the layer-by-layer spin-spray in-situ thermally polymerized imidazole tetrazolium crystalline composite glass fiber membrane F.

[0054] Step 6: After drying the prepared composite glass fiber diaphragm F in a vacuum drying oven at 60°C for 12 hours, remove it and place it in a glove box where the water and oxygen values ​​are both less than 0.01 ppm.

[0055] Example 4: A method for preparing a composite glass fiber diaphragm, the specific steps of which are as follows:

[0056] Step 1: Dissolve zinc nitrate hexahydrate in N,N-dimethylformamide (DMF) and sonicate for 15 minutes to disperse it into a colorless and transparent solution A with a concentration of 0.125 mol / L. Then, weigh out 5-aminotetrazole and 5,6-dimethylbenzimidazole in a molar ratio of 1:1, dissolve them together in DMF, and sonicate for 15 minutes to disperse them into a light yellow and clear solution B with a concentration of 0.125 mol / L.

[0057] Step 2: The glass fiber is cut into 4cm x 4cm squares, tailored to the size of a pouch battery. The glass fiber is placed on a 150℃ heating plate, with the spray gun 8cm away from the fiber. Solution A is evenly sprayed using the spray gun for 30 seconds. After standing for 20 seconds to stabilize, it is washed with ethanol. Solution B is then evenly sprayed using the spray gun for 30 seconds, and after standing for 20 seconds to stabilize, it is washed with ethanol. This process of layer-by-layer in-situ spraying (5 revolutions) yields composite glass fiber C.

[0058] Step 3: At room temperature, C is immersed in DMF for 3 hours, then removed and immersed in ethanol for 12 hours. The composite membrane is then placed in an oven at 120°C to dry, thus obtaining composite glass fiber D loaded with imidazole tetrazolium crystalline MOF.

[0059] Step 4: Prepare the precursor solution. The mass ratio of monomer: crosslinking agent: initiator is 9:1:1. Weigh 4-acryloylmorpholine monomer into a small bottle, then add crosslinking agent N,N-methylenebisacrylamide and initiator azobisisobutyronitrile and mix. Stir evenly at room temperature to form precursor solution E.

[0060] Step 5: 500 μl of precursor solution E is dropped into the prepared MOF composite glass fiber D to uniformly wrap the glass fiber. Then, it is placed in an 80℃ oven for in-situ thermal polymerization for 8 hours to finally obtain the layer-by-layer spin-spray in-situ thermally polymerized imidazole tetrazolium crystalline composite glass fiber membrane F.

[0061] Step 6: After drying the prepared composite glass fiber diaphragm F in an 80°C vacuum drying oven for an hour, remove it and place it in a glove box where the water and oxygen values ​​are both less than 0.01 ppm.

[0062] Example 5: A method for preparing a composite glass fiber diaphragm, the specific operation steps are as follows:

[0063] Step 1: Dissolve zinc nitrate hexahydrate in N,N-dimethylformamide (DMF) and sonicate for 10 minutes to disperse it into a colorless and transparent solution A with a concentration of 0.125 mol / L. Then, weigh out 5-aminotetrazole and 5,6-dimethylbenzimidazole in a molar ratio of 1:1, dissolve them together in DMF, and sonicate for 10 minutes to disperse them into a light yellow and clear solution B with a concentration of 0.125 mol / L.

[0064] Step 2: The glass fiber is cut into 19mm diameter circles to match the CR2032 battery casing. The glass fiber is placed on a 130℃ heating plate, with the spray gun 10cm away from it. Solution A is evenly sprayed using the spray gun for 40 seconds. After standing for 20 seconds to stabilize, it is washed with ethanol. Then, solution B is evenly sprayed using the spray gun for 80 seconds, and after standing for 20 seconds to stabilize, it is washed with ethanol. This process of layer-by-layer in-situ spraying for 20 revolutions yields composite glass fiber C.

[0065] Step 3: At room temperature, C is immersed in DMF for 2 hours, then removed and immersed in ethanol for 12 hours. The composite membrane is then placed in an oven at 120°C to dry, thus obtaining composite glass fiber D loaded with imidazole tetrazolium crystalline MOF.

[0066] Step 4: Prepare the precursor solution. The mass ratio of monomer: crosslinking agent: initiator is 8:1:1. Weigh 4-acryloylmorpholine monomer and place it in a small bottle. Then add crosslinking agent N,N-methylenebisacrylamide and initiator azobisisobutyronitrile and mix. Stir evenly at room temperature to form precursor solution E.

[0067] Step 5: 150 μl of precursor solution E is dropped into the prepared MOF composite glass fiber D to uniformly wrap the glass fiber. Then, it is placed in an 80℃ oven for in-situ thermal polymerization for 8 hours to finally obtain a layer-by-layer spin-spray in-situ thermally polymerized imidazole tetrazolium crystalline composite glass fiber membrane F.

[0068] Step 6: After drying the prepared composite glass fiber diaphragm F in a vacuum drying oven at 60°C for 12 hours, remove it and place it in a glove box where the water and oxygen values ​​are both less than 0.01 ppm.

[0069] Example 1 above is the best embodiment. The following are the experimental data of the product prepared in Example 1:

[0070] like Figure 2 As shown, after repeated layer-by-layer spin-spraying of metal salt solution and ligand solution, a large number of MOF inorganic particles are loaded inside the glass fiber. Among them, the Zn content in MOF accounts for 31.9%, the N content accounts for 5.9%, and the Si content in glass fiber accounts for 36.0%. It can be concluded that MOF is successfully loaded in glass fiber. The uniform distribution of MOF particles can be seen from the high-resolution image.

[0071] like Figure 3 As shown, the polymer successfully encapsulates the MOF-loaded composite glass fiber, reducing surface roughness.

[0072] like Figure 4 The figure shows the charge-discharge specific capacity and coulombic efficiency of a MOF composite glass fiber membrane sodium-ion battery after 900 cycles at a 1C current density. It can be seen that the charge-discharge capacity at a high current density of 1C is 108 mAh g⁻¹. -1 Its Coulomb efficiency is 99%.

[0073] like Figure 5 The figure shows the rate-of-charge (ROC) curves after 10 cycles at different current densities. The MOF composite glass fiber separator exhibits charge-discharge specific capacities of 113, 111, 109, 106, and 103 mAh g⁻¹ at current densities of 0.1C, 0.2C, 0.5C, 1C, and 2C, respectively. -1 The efficiency is close to 100%. This is due to the synthesized MOF material containing multiple nitrogen and amino functional groups, which has excellent multi-nitrogen three-dimensional channels and functional group modifiability, and can accelerate the uniform transport of sodium ions.

[0074] like Figure 6 As shown, the electrochemical window test of the assembled half-cell with glass fiber loaded MOF material was performed on an electrochemical workstation. It can be seen that the electrochemical window of the prepared membrane is 4.84V, which is a good electrochemical window.

[0075] like Figure 7 The figure shows the electrochemical impedance spectroscopy (EIS) test of the sodium battery containing a polynitrogen and amino composite membrane prepared in this invention before cycling, under an electrochemical workstation. The frequency range is 0.01-100000 Hz. The figure shows that the charge transfer resistance before cycling is 68 Ω, indicating a low initial internal resistance, which also demonstrates that the membrane material of the sodium battery containing the polynitrogen and amino composite membrane has low impedance.

[0076] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention shall still fall within the protection scope of the present invention.

Claims

1. A method for preparing a composite glass fiber diaphragm, characterized in that, The specific steps are as follows: S1: Dissolve zinc nitrate hexahydrate in N,N-dimethylformamide and disperse it by ultrasound to prepare a colorless and transparent solution A; then weigh 5-aminotetrazole and 5,6-dimethylbenzimidazole in a molar ratio of 1:1 and dissolve them together in N,N-dimethylformamide, disperse them by ultrasound to prepare a light yellow and clear solution B. S2: Place the glass fiber on the heating plate, spray solution A evenly onto it using a spray gun, let it stand and stabilize, then wash it with ethanol. Then spray solution B evenly onto it using a spray gun, let it stand and stabilize, then wash it with ethanol to obtain composite glass fiber C. S3: At room temperature, immerse composite glass fiber C in N,N-dimethylformamide for 1-3 hours, remove, then immerse in ethanol for 12-24 hours, remove; place the treated composite glass fiber C at 120°C. o The glass fiber D, which is a MOF composite loaded with imidazole-tetrazole crystals, is obtained by drying in oven C. S4: Preparation of precursor solution; Weigh 4-acryloylmorpholine monomer into a vial, then add crosslinking agent N,N-methylenebisacrylamide and initiator azobisisobutyronitrile and mix them in a mass ratio of 8:1:1 or 9:1:

1. Stir evenly at room temperature to form precursor solution E; S5: The precursor solution E is dropped into the prepared MOF composite glass fiber D, and then placed in an oven for in-situ thermal polymerization to finally obtain the composite glass fiber membrane F; after vacuum drying, it is placed in a glove box.

2. The method for preparing a composite glass fiber diaphragm according to claim 1, characterized in that: In step S1, the ultrasound time is 10-15 minutes.

3. The method for preparing a composite glass fiber diaphragm according to claim 2, characterized in that: In step S2, the temperature of the heating plate is 120-150°C. o C. The distance between the spray gun and the fiberglass is 8-10 cm.

4. The method for preparing a composite glass fiber diaphragm according to claim 3, characterized in that: In step S2, the spraying time for solution A is 20-30 seconds and the stabilization time is 10-20 seconds, while the spraying time for solution B is 30-40 seconds and the stabilization time is 20-30 seconds.

5. The method for preparing a composite glass fiber diaphragm according to claim 4, characterized in that: In step S5, the temperature of the oven is 65-80℃.

6. The method for preparing a composite glass fiber diaphragm according to claim 5, characterized in that: In step S5, the vacuum drying temperature is 60-80℃, and the oxygen level in the glove box is not higher than 0.01ppm.

7. The method for preparing a composite glass fiber diaphragm according to claim 6, characterized in that: In step S5, for the button cell 2032, the MOF composite glass fiber D is cut into a circle with a diameter of 19 mm, and the amount of the precursor solution added is not less than 100 μL.

8. The method for preparing a composite glass fiber diaphragm according to claim 6, characterized in that: In step S5, for the soft-pack battery, the glass fiber D of the MOF composite is cut into a square of 4cm*4cm, and the amount of the precursor solution added is not less than 500μL.

9. A composite glass fiber diaphragm prepared by the preparation method according to claim 1.

Citation Information

Patent Citations

  • Preparation method and application of TiN surface modified glass fiber diaphragm

    CN116706422A

  • High-strength composite material solid electrolyte, preparation method thereof and application of high-strength composite material solid electrolyte in electrochromic device

    CN113897007A

  • Holocellulose composite diaphragm for sodium ion battery as well as in-situ preparation method and application of holocellulose composite diaphragm

    CN114597580A